2009
DOI: 10.2165/11318890-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Interventions that can Reduce Inappropriate Prescribing in the Elderly

Abstract: Inappropriate prescribing of medicines may lead to a significant risk of an adverse drug-related event. In particular, prescribing may be regarded as inappropriate when alternative therapy that is either more effective or associated with a lower risk exists to treat the same condition. This review aims to identify interventions and strategies that can significantly reduce inappropriate prescribing in the elderly. The review is based on a search of electronic databases using synonyms of keywords such as 'elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
218
0
18

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(245 citation statements)
references
References 50 publications
9
218
0
18
Order By: Relevance
“…Several interventions have been suggested to improve the quality of prescribing in the elderly (255).…”
Section: Discussionmentioning
confidence: 99%
“…Several interventions have been suggested to improve the quality of prescribing in the elderly (255).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of such interventions found mixed results [38] and especially singled out limitations of several studies as they did not define what data would be required to assess adequacy for a given level of intervention nor sample size calculations to determine acceptable type I and type II errors. Another review also suggested that mere dissemination of guidelines is unlikely to be effective, whereas active educational interventions in the form of workshops, meetings, and regular reports could improve drug treatment [39].…”
Section: Educational Interventionsmentioning
confidence: 99%
“…However, although two recent systematic reviews found evidence that the use of such systems can produce improvements in prescribing and dispensing practices, no evidence was provided on the administration of medication (Kaur et al 2009, Yourman et al 2008. In terms of the impact of barcode medication systems on medication administration errors, another review by Paoletti et al (2007) concluded that there is evidence of a reduction in medication administration errors in hospitals, but evidence for care homes is extremely limited…”
Section: Literature Reviewmentioning
confidence: 99%